Clinical and bi-genomic DNA findings of patients suspected to have mitochondrial diseases - Gedikbasi, Asuman; Toksoy, Guven; Karaca, Meryem; Gulec, Cagri; Balci, Mehmet Cihan; Gunes, Dilek; Gunes, Seda; Aslanger, Ayca Dilruba; Unverengil, Gokcen; Karaman, Birsen; Basaran, Seher; Demirkol, Mubeccel; et al. (Frontiers in Genetics, 2023)
Background. Mitochondrial diseases are the most common group of inherited metabolic disorders, sheltering difficulties in definite diagnosis due to clinical and genetic heterogeneity. Clinical components are predominantly associated with pathogenic variants shown in nuclear or mitochondrial genomes that affect vital respiratory chain function. The development of high-throughput sequencing technologies has accelerated the elucidation of the genetic etiology of a number of genetic diseases that previously remained undiagnosed. Methods. Thirty affected patients from 24 unrelated families with clinical, radiological, biochemical, and histopathological evaluations considered for mitochondrial diseases were investigated. DNA isolated from peripheral blood samples of probands was sequenced for nuclear exome and mitochondrial DNA (mtDNA) analysis. mtDNA sequencing was also performed from the muscle biopsy material in one patient. For segregation, Sanger sequencing is performed for pathogenic alterations in five other affected family members and healthy parents. Results. Exome sequencing revealed 14 different pathogenic variants in genes encoding mitochondrial function peptides (AARS2, EARS2, ECHS1, FBXL4, MICOS13, NDUFAF6, POLG, TK2, OXCT1) in 12 patients from nine families and four variants in genes encoding important for muscle structure (CAPN3, DYSF, TCAP) in six patients from four families. Three probands carried pathogenic mtDNA variations in two genes (MT-ATP6 and MT-TL1). Nine variants in five genes are first-time reported with disease association (AARS2: c.277C>T/p.(Arg93*), c.845C>G/ p.(Ser282Cys); EARS2: c.319C>T/p.(Arg107Cys), c.1283delC/p.(Pro428Leufs*); ECHS1: c.161G>A/p.(Arg54His); c.202G>A/p.(Glu68Lys); NDUFAF6: c.479delA/p.(Asn162Ilefs*27); OXCT1: c.1370C>T/p.(Thr457Ile), c.1173-139G>T/p.(?). Conclusion. Bi-genomic DNA sequencing clarified genetic etiology in 67% (16/24) of the families. Diagnostic utility by mtDNA sequencing in 3% (3:24) and exome sequencing in 40% (13:24) of the families prioritized searching for nuclear genome pathologies for the first-tier test. Weakness and muscle wasting revealed in 17% (4/24) of the families underlined that Limb-Girdle muscular dystrophy, mimicking mitochondrial myopathy, is an essential point for differential diagnosis. The correct diagnosis is crucial for comprehensive genetic counseling of families. Also, it contributes to making treatment-helpful referrals, such as ensuring early access to medication for patients with mutations in the TK2 gene.